ISOLASI BAKTERI ENDOFIT DARI TUMBUHAN KELAKAI (Stenochlaena palustris (Burm) Bedd). - Oksal, Efriyana; Ngazizah, Febri Nur; chuchita; Irawan, Ahmad; Pereiz, Zimon (Jurnal Insan Farmasi Indonesia, 2024)
Kelakai (Stenochlaena palustris) is a type of medicinal fern used by the Dayak ethnic community in traditional medicine. The diverse bioactivity of kelakai is closely related to its high antioxidant content. The phytochemical compounds found in kelakai, such as phenols, flavonoids, anthocyanins, hydroxycinnamic acid, proanthocyanidins, tannins, alkaloids, saponins, carotenoids, and terpenoids, are believed to be produced by the endophytic microbes present in kelakai. Endophytic bacteria can be isolated from the plant, such as leaves, stems, bark, and roots. This research aims to isolate and identify endophytic bacteria from S. palustris. The method used is direct planting. The samples used are the leaves and stems of S. palustris. The results of the research conducted revealed six isolates of endophytic bacteria found in the leaves and stems, namely D1, D2, B1, B2, B3, and B4, which exhibit different colony morphology on the surface and color, while having similar shapes and edges. The results of the Gram staining test on the endophytic bacteria showed negative results and they are rod-shaped. In this study, endophytic bacteria S. palustris were successfully obtained from leaves and stems, which can be further analyzed for their activity.